Modern Methods for Diagnosing Dysfunction of the Temporomandibular Joint and Parafunction of the Masticatory Muscles - Aliev Navruz Khasanovich (American Journal of Biology and Natural Sciences, 2024)
A literature review is devoted to the study of improving the methods of clinical and functional assessments and diagnosing the pathological condition of the temporomandibular joint (TMJ). The pathology of TMJ occupies a special place among dental diseases due to the significant prevalence, extremely diverse and complex clinical picture. According to clinical studies, TMJ pathology occurs in 70-80% of the healthy population and is in third place after caries and periodontal disease. Throughout life, each person experienced certain symptoms of dysfunction, manifested by pain in the chewing muscles or clicking in the TMJ. The complexity of the anatomical structure, the large number and originality of the course options, the variety of clinical symptoms of pathological processes make it difficult to diagnose TMJ diseases. Diagnosis of TMJ diseases remains one of the difficult issues of dentistry. Based on this, the authors analyze a number of scientific and literary information and conclude that the diagnosis and differentiation of a TMJ disorder is a very complicated process and combined methods of examining these patients are required.